Bhāratīya krānti āṇi rāshṭrasabhā - Jāvaḍekara, Śaṅkara Dattātraya, 1894-1955 (SAMP early 20th-century Indian books project ;, 1946)
On major revolutionary movements during the Indian freedom struggle and the attitude of the Indian National Congress towards them.